THE USE OF VERBAL HUMOR OF THE MAIN CHARACTER JAKE PERALTA - Muh. Fauzan Fahriyah Pattisahusiwa; Yunitari Mustikawati; Fitriyani Bakri (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This study aims to identify the verbal humor techniques employed by Jake Peralta and explain the function of humor in his interactions with other characters. This study uses a qualitative descriptive method with Berger's (1993) humor technique theory to analyze the verbal humor techniques employed by Jake Peralta and and Nilsen & Nilsen's (2018) humor function theory to analyze the functions of verbal humor used by Jake Peralta. Data were taken from Jake Peralta's dialogues in nine episodes selected purposively. The results show that there are 13 humor techniques, including puns, sarcasm, irony, ridicule, insults, facetiousness, exaggeration, absurdity, ignorance, impersonation, imitation, mimicry, and parody. In terms of the function of humor, it was found that the social function was the most common, followed by the psychological function. Jake Peralta used verbal humor to create a more relaxed working atmosphere, strengthen relationships with his colleagues, and ease tension in stressful situations. These results show that Jake Peralta's verbal humor is not just entertainment, but also an important communication strategy in building character dynamics and storyline in Brooklyn Nine-Nine.